Analysis Determination Of Business Communication, Trust And Price On Purchasing Decisions Of Spare Parts At PT. Autostar Mandiri Teknotama - Agusman Agusman; Victor Victor; Laura Tifani (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to explore the impact of business communication, trust, and price on purchasing decisions at PT Autostar Mandiri Teknotama. The research method used is associative descriptive with a population of 83 customers of the company. Sampling was conducted using a saturated sample technique, and data were collected through questionnaires. Analysis was performed using descriptive statistics, data quality tests, classical assumption tests, multiple regression analysis, hypothesis testing, and coefficient of determination using the SPSS program. The results showed that simultaneously, the F value of 357.532 was greater than the critical F value of 3.11 with a significance level of 0.000 < 0.05, indicating that the hypothesis was accepted, demonstrating a positive and significant influence of business communication, trust, and price together on purchasing decisions. Partially, hypothesis testing revealed that business communication (t = 2.040), trust (t = 2.774), and price (t = 3.202) each had a positive and significant impact on purchasing decisions, with significance levels of 0.045, 0.007, and 0.002, respectively. Therefore, the conclusion of this study is that business communication, trust, and price, either partially or collectively, significantly influence purchasing decisions at PT Autostar Mandiri Teknotama.